Treasury System Design : A Value Chain Approach - Tandberg, Eivind (Washington, D.C. : International Monetary Fund, 2005)
Treasury systems enable governments to prepare financial plans, implement annual budgets, handle cash resources, provide fiscal accounts, and ensure control and accountability. The design of these systems varies considerably across countries, reflecting differences in priorities, country capacities, and political traditions. The paper develops a generic value chain for a treasury system and discusses the choices that are made in designing that system. The paper provides an indicative set of good practices for treasury design in different groups of countries. The generic model and the proposed good practices are compared to the actual treasury systems in seven countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet